Monoubiquitination of syntaxin 5 regulates Golgi membrane dynamics during the cell cycle - Huang, Shijiao (Dev Cell, 2016)
The Golgi apparatus undergoes a ubiquitin-dependent disassembly and reassembly process during each cycle of cell division. Here we report the identification of the Golgi t-SNARE syntaxin 5 (Syn5) as the ubiquitinated substrate. Syn5 is monoubiquitinated by the ubiquitin ligase HACE1 in early mitosis and deubiquitinated by the deubiquitinase VCIP135 in late mitosis. Syn5 ubiquitination on Lysine 270 (K270) in the SNARE domain impairs the interaction between Syn5 and the cognate v-SNARE Bet1, but increases its binding to p47, the adaptor protein of p97. Expression of the Syn5 K270R mutant in cells impairs post-mitotic Golgi reassembly. Therefore, monoubiquitination of Syn5 in early mitosis disrupts SNARE complex formation. Subsequently, ubiquitinated Syn5 recruits p97/p47 to the mitotic Golgi fragments and promotes post-mitotic Golgi reassembly upon ubiquitin removal by VCIP135. Overall, this study reveals both the substrate and the mechanism of ubiquitin-mediated regulation of Golgi membrane dynamics during the cell cycle.